ANTIHIPERPIGMENTASI Hylocereus costaricensis MELALUI INHIBISI TIROSINASE: STUDI NETWORK PHARMACOLOGY DAN MOLECULAR DOCKING - Prasetyo, Bayu Febram; Alauddin, Daffa Rizal Dzulfaqaar; Purwono, Rini Madyastuti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Hyperpigmentation was driven by increased melanogenesis and oxidative stress, creating a need for effective and safe depigmenting candidates. This study aimed to identify bioactive compounds from Hylocereus costaricensis, to map hyperpigmentation-related targets and pathways using network pharmacology, and to evaluate the binding potential of selected compounds to a melanogenesis target using molecular docking. The workflow included compound screening and drug-likeness/ADMET evaluation, prediction of compound targets and hyperpigmentation-associated genes, construction of compound–target–disease and protein–protein interaction networks, topological and GO/KEGG enrichment analyses, and docking to TYRP1 (PDB: 5M8O). Five main candidates, namely 2,2-dimethyl-3-phenylpropanoic acid, ferulic acid, o-coumaric acid, p-coumaric acid, and vanillic acid, have met the initial criteria. Network pharmacology highlighted a multi-target mechanism by prioritizing key nodes including AKT1, EGFR, PIK3CA, TYR, and CDK4 and by indicating enriched signaling pathways relevant to pigmentation regulation and oxidative-stress responses. Docking results showed moderate affinities, with binding energies of approximately −6.551 to −6.184 kcal/mol and estimated inhibition constants of 15.779 to 29.315 µM, and 2,2-dimethyl-3-phenylpropanoic acid yielded the best score among the tested ligands. Overall, the integrated network pharmacology–docking strategy provided a rational prioritization of compounds and targets for developing anti-hyperpigmentation agents derived from H. costaricensis; however, the evidence remained preliminary and required further experimental validation and mechanistic confirmation.